Technology Acceptance in Medical Education: A Review - Asghar, Muhammad Ahmad (Kashmir Journal of Academic Research and Development, 2025)
Medical education technology acceptance is the manner in which learners, teachers and institutions embrace and incorporate the use of digital tools, sites and innovations in the teaching and learning activities. Within the last twenty years, the academic healthcare has been redefined by the fast technology development in healthcare and e-learning, with blended learning, simulation, virtual reality (VR), mobile learning, and online assessment systems as key contributors. It is important to know the determinants, which include the perceived usefulness, ease of use, attitude, subjective norms and facilitating conditions in order to maximize the potential of education technology in the medical training. The review discusses articles published in 2000-2025 with particular attention to Pakistani medical education. The results indicate that the infrastructure quality, the level of faculty skills, student motivation, the cultural attitude, and institutional support is relevant in the technology acceptance. The problems of resource-limited environments remain. This review describes the theoretical concepts (e.g., TAM, UTAUT), results of the international and national research, and suggests recommendations to improve the implementation.